Building iPhone OS Accessories Use the iPhone Accessories API to Control and Monitor Devices - Maskrey, Ken (Apress : Imprint: Apress, 2010)
This book provides a serious, in-depth look at Apple's External Accessory framework and the iPhone Accessories API. You'll learn how to create new, integrated solutions that combine iPhone apps with dedicated hardware. The iPhone OS Accessories API expands the opportunities for innovative iPhone developers, allowing you to control and monitor external devices, whether you've built them yourself or obtained them from a third party.